Indywidualne konta emerytalne jako dobrowolne forma gromadzenia oszczędności emerytalnych - Kubiak, Damian (Individual pension account programmes as a voluntary forms of saving for old age, 2007)
Individual pension (retirement) account programmes (IKE) are voluntary forms of saving for old age. They have been on Polish market since 2004. They are regulated by the Act of 20 April 2004 on Individual Retirement Accounts. IKE is maintained as one of four following forms of agreements: with an investment fund, with a broker, for the provision of brokerage services, with an insurance company and with a bank. At present IKE are not so popular in Poland. With around 0.85 million participants. Amount of savings exceeded 1,3 billion of PLZ which equals the amount of 1.5 thousand PLZ per participant. This is much less than Polish government expected.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1186, s. 53-62